Transplant program evaluations in the middle of the COVID‐19 pandemic. Issue 11 (4th July 2022) - Miller, Jonathan; Lyden, Grace R.; Zaun, David; Kasiske, Bertram L.; Hirose, Ryutaro; Israni, Ajay K.; Snyder, Jon J.
Abstract : Potential regional variations in effects of COVID‐19 on federally mandated, program‐specific evaluations by the Scientific Registry of Transplant Recipients (SRTR) have been controversial. SRTR January 2022 program evaluations ended transplant follow‐up on March 12, 2020, and excluded transplants performed from March 13, 2020 to June 12, 2020 (the "carve‐out"). This study examined the carve‐out's impact, and the effect of additionally censoring COVID‐19 deaths, on first‐year posttransplant outcomes for transplants from July 2018 through December 2020. Program‐specific hazard ratios (HRs) for graft failure and death estimated under two alternative scenarios were compared with published HRs: (1) the carve‐out was removed; (2) the carve‐out was retained, but deaths due to COVID‐19 were additionally censored. The HRs estimated by censoring COVID‐19 deaths were highly correlated with those estimated with the carve‐out alone ( r 2  = .96). Removal of the carve‐out resulted in greater variation in HRs while remaining highly correlated ( r 2  = .82); however, little geographic impact of the carve‐out was observed. The carve‐out increased average HR in the Northwest by 0.049; carve‐out plus censoring reduced average HR in the Midwest by 0.009. Other regions of the country were not significantly affected. Thus, the current COVID‐19 carve‐out does not appear to impart substantial bias based on the region of the country. Abstract : The Scientific Registry of Transplant Recipients explores alternative scenarios for handling COVID‐19 deaths and finds little evidence of geographic bias due to any of the strategies since neither removing the current carve‐out strategy nor additionally censoring for COVID‐19 deaths significantly impacted the January 2022 transplant program evaluations.